National legal regulation of the digital economy and information platforms - Dunayev, Ihor; Orlov , Oleksandr (Pressing Problems of Public Administration, 2023)
This article serves as a logical continuation of the authors’ series of publications on the public regulation of information platforms and platform economies. The objective of this article is to provide a concise summary of the rich international experience in national legal regulation of the digital economy and information platforms while identifying pertinent models of such regulation. It further contributes to the ongoing extensive expert and policy debate regarding what, how, and whom to regulate in the new platform environment, in which nearly everyone participates or will soon be involved. Drawing on a comprehensive analysis of legislation in foreign jurisdictions, the article highlights and elucidates three main models of legal regulation for the digital economy, using examples: the model of legislative regulation of the digital economy, the national strategic model, and the regional strategic model. The conclusion is drawn that Ukraine exhibits significant features that largely correspond to the first model. Such a model may involve the creation of specific legislation aimed at digital sector development, stimulating innovation and supporting startups. Nevertheless, Ukraine has already begun to encounter limitations associated with this model, as the digital economy evolves more rapidly than the government and legislators can adapt the legal framework to the latest changes, resulting in regulatory gaps.